Boxing, Masculinity and Identity - Woodward, Kath (Taylor & Francis, 2007)
Boxing is infused with ideas about masculinity, power, race and social class, and as such is an ideal lens through which social scientists can examine key modern themes. In addition, its inherent contradictions of extreme violence and beauty and of discipline and excess have long been a source of inspiration for writers and film makers. Essential reading for anyone interested in the sociology of sport and cultural representations of gender, Boxing, Masculinity and Identity brings together ethnographic research with material from film, literature and journalism. Through this combination of theoretical insight and cultural awareness, Woodward explores the social constructs around boxing and our experience and understanding of central issues including: masculinity mind, body and the construction of identity spectacle and performance: tensions between the public and private person boxing on film: the role of cultural representations in building identities methodologies: issues of authenticity and 'truth' in social science.